2002
DOI: 10.1007/s00216-002-1387-7
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline-8-ol-immobilized Amberlite XAD-4: Synthesis, characterization, and uranyl ion uptake properties suitable for analytical applications

Abstract: Amberlite XAD-4 has been functionalized by coupling it with 5-aminoquinoline-8-ol after acetylation. The resulting resin has been characterized by elemental analysis and IR spectra and has been used for preconcentrating uranyl ions prior to its determination by spectrophotometry. The optimum pH value for quantitative sorption is 4-6, and desorption can be achieved by using 5 mL of 1 mol L(-1) HCl. The sorption capacity of the resin is 11.5 mmol g(-1). The effect of various cations and anions on the preconcentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…More significantly, these results indicated that the improvement of uranium (VI) extraction is achievable by an imprinting procedure for the functionalized chitosan. Furthermore, the retention capacities of ion-imprinted or non-imprinted HQ-type chitosan resins in the present study are higher than other quinoline-8-ol impregnated 16 and anchored 17 polystyrene divinylbenzene resins, suggesting the advantages of chitosan over other synthetic base materials.…”
Section: Retention or Sorption Capacity For Uranium (Vi)mentioning
confidence: 51%
See 1 more Smart Citation
“…More significantly, these results indicated that the improvement of uranium (VI) extraction is achievable by an imprinting procedure for the functionalized chitosan. Furthermore, the retention capacities of ion-imprinted or non-imprinted HQ-type chitosan resins in the present study are higher than other quinoline-8-ol impregnated 16 and anchored 17 polystyrene divinylbenzene resins, suggesting the advantages of chitosan over other synthetic base materials.…”
Section: Retention or Sorption Capacity For Uranium (Vi)mentioning
confidence: 51%
“…Recently, Oshita and co-workers 12 synthesized several novel chitosan resins derivatized with serine moiety, phenylarsonic acid moiety, 13 iminodi(methylphosphonic acid) moiety 14 and 3,4-dihydroxybenzoic acid 15 for collection/pre-concentration of uranium, which offered excellent uranium retention capacities of 49.4, 83, 117.5 and 330 mg g -1 resin, respectively. Quinoline-8-ol moiety has been immobilized in amberlite XAD-4 16 and anchored in chloromethylated polymeric resin beads, 17 which offered uranium retention capacities of 2.74 and 120.3 mg g -1 , respectively. Inoue and co-workers have prepared Ga templated quinoline-8-ol chitosan and investigated its adsorption of Mo(IV), V(IV), In(III), Al(III), Zn(II), Fe(II), Cd(II), and Ga(III).…”
mentioning
confidence: 99%
“…As can be seen in Table 3, the adsorption capacity of the resin for U(VI) ions using the column method is higher than chelate modified and/or imprinted SPE procedures reported in the literature up to now. 6,[29][30][31] However, even higher adsorption capacities (>0.102 mmol g -1 ) have been reported in the literature in similar studies using the batch method. 10,18,22 On the other hand, the resin can be successfully regenerated in over 250 operating cycles by the column method without any loss in its sorption capacity.…”
Section: Adsorption Isotherm and Adsorption Capacitymentioning
confidence: 87%
“…3 Several methods for determination of uranium based on the preconcentration techniques have been reported. Solid sorbents such as neutral polymer-Amberlite XAD series, 4 silica, 5 activated silica gel, 6 polyurethane foam 7 and cationic and anionic exchange resins 8 have been reported for the enrichment of uranium(VI) from dilute solutions prior to determination by a variety of analytical techniques.…”
Section: Introductionmentioning
confidence: 99%